The Effect of Plyometric Box Jump and Hurdle Hopping Exercises on Limb Muscle Explosive Power in a High School Volleyball Team - Felinda Sari; Eka Pratiwi Yunianti; Satria Armanjaya (Universitas Majalengka, 2023)
Leg muscle strength is needed in volleyball. The purpose of this study was to determine the effect of plyometric box jump and plyometric hurdle hopping exercises on the explosive power of the leg muscles in the volleyball team at SMA Negeri 1 Sumberejo. The method used is experimental. The sample used was 30 students. Data analysis using prerequisite tests and t tests. The results showed that the effect of the plyometric box jump exercise t count was -7.63 > t table = 1.753, and the effect of the plyometric hurdle hopping exercise t count was -10.21 > t table = 1.753. It was concluded that the plyometric box jump and plyometric hurdle hopping exercises had an effect on the muscles and limbs of the volleyball team of SMA Negeri 1 Sumberejo. Of the two exercises, the plyometric hurdle hopping exercise has a greater effect when compared to the plyometric box jump, or it can be concluded that there is no difference between the two exercise treatments.